proof left as an exercise
06-06-2022, 11:41 PM
Post: #1
 Thomas Klemm Senior Member Posts: 1,599 Joined: Dec 2013
proof left as an exercise
Just stumbled upon this and thought some of you might enjoy solving this as well.
Quote:Prove that the following expression can be expressed as being identical to a single standard trigonometric function of an integer input with all inputs being in degrees.
You may use a calculator or trig table as a guide, but the results from the calculator or trig table will not be accepted as part of the proof.

\begin{align} \frac{2\cos(30^{\circ})}{1+4\sin(70^{\circ})} = \,? \end{align}
06-07-2022, 05:05 AM
Post: #2
 Ángel Martin Senior Member Posts: 1,316 Joined: Dec 2013
RE: proof left as an exercise
not a proof but it's equal to: tan(20), right?
06-07-2022, 05:32 AM
Post: #3
 Thomas Klemm Senior Member Posts: 1,599 Joined: Dec 2013
RE: proof left as an exercise
Correct, that was the calculator or trig table part.
06-07-2022, 05:36 PM
Post: #4
 Albert Chan Senior Member Posts: 1,839 Joined: Jul 2018
RE: proof left as an exercise
Proof: 2*cos(30°) / (1 + 4*sin(70°)) = tan(20°)

2*cos(30°) / (1 + 4*cos(20°)) ?=? tan(20°)             // sin(70°) = cos(20°)
2*cos(30°) ?=? tan(20°) + 4*sin(20°)                     // cross multiply
cos(20°)*cos(30°) ?=? sin(20°)/2 + sin(40°)            // multiply by cos(20°)/2
sin(40°) ?=? cos(20°)*cos(30°) - sin(20°)*sin(30°)

cos(50°) = cos(20°+30°)                                       // trig angle sum identity

Proof is complete, (read it bottom-up)
06-07-2022, 06:17 PM
Post: #5
 Albert Chan Senior Member Posts: 1,839 Joined: Jul 2018
RE: proof left as an exercise
Top-down proof (equivalent to previous post)

2*cos(30°) / (1+4*sin(70°))
= cos(30°) / (sin(30°) + 2*cos(20°))
= sin(20°)*cos(30°) / (sin(20°)*sin(30°) + sin(40°))
= sin(20°)*cos(30°) / (sin(20°)*sin(30°) + cos(50°))
= sin(20°)*cos(30°) / (cos(20°)*cos(30°))
= tan(20°)
06-08-2022, 01:50 AM
Post: #6
 Albert Chan Senior Member Posts: 1,839 Joined: Jul 2018
RE: proof left as an exercise
Another proof, letting t = tan(10°)

tan(30°) = 1/√3 = (3t-t³) / (1-3t²)                  // triple-angle formula
⇒ t³ = √3*t² + 3t - 1/√3
⇒ t4 = 6t² + 8/√3*t - 1

2*cos(30°) / (1 + 4*cos(20°)) ?=? tan(20°)

√3 / (1 + 4*(1-t²)/(1+t²)) ?=? 2t / (1-t²)        // tangent half-angle formula
√3*(1+t²) / (5-3t²) ?=? 2t / (1-t²)                  // cross multiply
√3*(1-t4) ?=? 10t - 6t³

√3*(1-t4) + 6t³ - 10t
= √3 - √3*(6t² + 8/√3*t - 1) + 6*(√3*t² + 3t - 1/√3) - 10t
= 0      QED
06-08-2022, 11:12 AM
Post: #7
 Albert Chan Senior Member Posts: 1,839 Joined: Jul 2018
RE: proof left as an exercise
(06-08-2022 01:50 AM)Albert Chan Wrote:  Another proof, letting t = tan(10°)

tan(30°) = 1/√3 = (3t-t³) / (1-3t²)                  // triple-angle formula
⇒ t³ = √3*t² + 3t - 1/√3

We could simplify previous proof, by getting t² in terms of t

t²*t = √3*t² + 3t - 1/√3
t² = (3t - 1/√3) / (t - √3)

2*cos(30°) / (1 + 4*cos(20°))
= √3 / (1 + 4*(1-t²)/(1+t²))
= (1/√3 - t) / (1 + (1/√3)*t)
= (tan(30°) - tan(10°)) / (1 + tan(30°)*tan(10°))
= tan(20°)
06-08-2022, 11:18 PM
Post: #8
 Thomas Klemm Senior Member Posts: 1,599 Joined: Dec 2013
RE: proof left as an exercise
We can use the triple angle formulae:

\begin{align} \sin(3 \theta) &= 3 \sin \theta - 4 \sin^{3} \theta \\ \cos(3 \theta) & = 4 \cos^{3}\theta - 3 \cos \theta \\ \end{align}

\begin{align} \sin(3 \theta) &= 3 \sin \theta - 4 \sin^{3} \theta \\ &= \sin \theta \, [3 - 4 \sin^{2} \theta] \\ &= \sin \theta \, [4 \cos^{2} \theta - 1] \\ \end{align}

$$2 \cos(3 \theta) - 1 = 8 \cos^{3}\theta - 6 \cos \theta - 1 \\$$

For $$\theta = 20^\circ$$ we get:

\begin{align} 2 \cos(3 \theta) - 1 &= \\ 2 \cos(3 \cdot 20^\circ) - 1 &= \\ 2 \cos(60^\circ) - 1 &= \\ 2 \cdot \tfrac{1}{2} - 1 &= 0 \\ \end{align}

And thus:

$$8 \cos^{3}(20^\circ) - 6 \cos(20^\circ) - 1 = 0$$

From this we conclude:

\begin{align} 8 \cos^{3}(20^\circ) - 2 \cos(20^\circ) &= 1 + 4 \cos(20^\circ) \\ 2 \cos(20^\circ) [4 \cos^{2}(20^\circ) - 1] &= 1 + 4 \cos(20^\circ) \\ \end{align}

Time to plug all that into the formula:

\begin{align} \frac{2\cos(30^{\circ})}{1+4\sin(70^{\circ})} &= \frac{2\sin(60^{\circ})}{1+4\cos(20^{\circ})} \\ \\ &= \frac{2\sin(3 \cdot 20^{\circ})}{1+4\cos(20^{\circ})} \\ \\ &= \frac{2 \sin(20^\circ) [4 \cos^{2}(20^\circ) - 1]}{2 \cos(20^\circ) [4 \cos^{2}(20^\circ) - 1]} \\ \\ &= \frac{\sin(20^\circ)}{\cos(20^\circ)} \\ \\ &= \tan(20^\circ) \end{align}

Or then we use the product to sum identity:

$$2 \cos \theta \cos \varphi = \cos(\theta + \varphi )+\cos(\theta - \varphi)$$

We use $$\cos(60^\circ) = \frac{1}{2}$$ and start with:

\begin{align} \cos(10^\circ) &= 2 \cos(60^\circ) \cos(10^\circ) \\ &= \cos(70^\circ) + \cos(50^\circ) \\ \\ \cos(50^\circ) + \cos(10^\circ) &= \cos(70^\circ) + 2 \cos(50^\circ) \\ 2 \cos(30^\circ) \cos(20^\circ) &= \sin(20^\circ) + 2 \sin(40^\circ) \\ &= \sin(20^\circ) + 4 \sin(20^\circ) \cos(20^\circ) \\ &= \sin(20^\circ)[1 + 4 \cos(20^\circ)] \\ \end{align}

\begin{align} \frac{2 \cos(30^\circ)}{1 + 4 \cos(20^\circ)} = \frac{\sin(20^\circ)}{\cos(20^\circ)} = \tan(20^\circ) \end{align}

Or then:

\begin{align} \frac{2 \cos(30^\circ)}{1 + 4 \sin(70^\circ)} = \tan(20^\circ) \end{align}
06-09-2022, 12:35 AM
Post: #9
 Albert Chan Senior Member Posts: 1,839 Joined: Jul 2018
RE: proof left as an exercise
(06-08-2022 11:18 PM)Thomas Klemm Wrote:  We can use the triple angle formulae:

\begin{align} \sin(3 \theta) &= 3 \sin \theta - 4 \sin^{3} \theta \\ \cos(3 \theta) & = 4 \cos^{3}\theta - 3 \cos \theta \\ \end{align}

I noticed an easier way

sin(3θ)/sin(θ) = 4*cos(θ)^2 - 1
cos(3θ)/cos(θ) = 4*cos(θ)^2 - 3

sin(3θ)/sin(θ) = cos(3θ)/cos(θ) + 2

This is all is need for the proof:

2*cos(30°) / (1+4*sin(70°))
= 2*sin(60°) / (1+4*cos(20°))
= 2*sin(20°) * (cos(60°)/cos(20°) + 2) / (1+4*cos(20°))
= tan(20°) * (1+4*cos(20°)) / (1+4*cos(20°))
= tan(20°)
 « Next Oldest | Next Newest »

User(s) browsing this thread: 1 Guest(s)